Bi-causality between gender inequality and wage gap and its impact on economic growth - Hazarika, Devasish; Satyakam, Shreedhar (Edelweiss Applied Science and Technology, 2024)
It is imperative that research be conducted on the intricate and important subject of how gender inequality and the pay gap connect to the development of India’s economy. There are significant differences between the genders in a range of social, health, educational, and professional possibilities in India, just as there are in many other regions of the globe. In India, this is also the case. The main factor that contributes to the gender pay gap is the fact that women get less money than men do for doing the same job. A cycle of gender inequality is maintained and exacerbated by the salary disparity that exists today. In addition, the gender pay gap restricts women’s ability to achieve economic independence, which in turn restricts their opportunities to pursue higher levels of education and healthcare. This has repercussions for the expansion of human capital, which plays an essential role in the development of the economy. Women who earn less than males are less inclined to invest in their own education and professional development, which in turn lowers the general level of competition in the labour market in developing countries.